Effect of Sowing Date on Grain Yield, its Components and Some Morpho-Phenological Traits of Durum Wheat (Triticum durum Desf.) In Semi-Arid Zone in Algeria - Oulmi, Abdelmalek; Frih, Benalia; Guendouz, Ali; Benkadja, Sarah (International Journal of Bio-resource and Stress Management, 2022)
This study was conducted at Setif Agricultural Experimental Station in 2017−2018 crop season, the experimental material used in this study consisted of 5 cultivars (Triticum durum Desf.) based on their difference between early and late cultivation. The genotypes tested were sowing in in a random block design with three replications, each plot consisted of 2 rows of 2.5 m long spaced of 20 cm. The aim of this study is to assess the impact of the choice of sowing date on grain yield, these components as well as some morpho-phenological traits in order to have an idea on the best sowing date. Two-way analysis of variance showed that the effect of sowing date was significant (p<0.001−0.05) with the variables above ground biomass (BIO), spike weight (SW), Thousand kernels weight (TKW), Flag leaf area (LA), plant height (PH), number of days to heading (DH) and canopy temperature (CT), this effect caused the decrease of major parameters studied and mainly grain yield (GY), accompanied by decrease of BIO, SW, TKW, relative Water contents RWC, LA, PH and DH. Ofanto is shown to be the most suitable genotype for the late sowing date (January). The correlation analysis show that GY was significantly, strongly and positively correlated (p<0.001) under both sowing date with BIO and SW. CT was negatively correlated with GY, BIO, SW and HI (p<0.05) who suggest that our plants underwent water stress during the second sowing date.